2015
DOI: 10.1371/journal.pone.0144007
|View full text |Cite
|
Sign up to set email alerts
|

Impaired H-Reflex Gain during Postural Loaded Locomotion in Individuals Post-Stroke

Abstract: ObjectiveSuccessful execution of upright locomotion requires coordinated interaction between controllers for locomotion and posture. Our earlier research supported this model in the non-impaired and found impaired interaction in the post-stroke nervous system during locomotion. In this study, we sought to examine the role of the Ia afferent spinal loop, via the H-reflex response, under postural influence during a locomotor task. We tested the hypothesis that the ability to increase stretch reflex gain in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…When demands for postural loads have been alleviated, the stroke-impaired system was capable of generating foot forces that are appropriately controlled in magnitude and direction [ 13 ]. However, this appropriate foot-force control capability was disrupted under more challenging conditions, when individuals post-stroke have to simultaneously control for postural loads in addition to the locomotor task [ 22 , 23 ], comparable to overground/treadmill walking conditions. This inability to modulate braking impulse with reduction in speed can pose safety threats for individuals with chronic post-stroke hemiparesis.…”
Section: Discussionmentioning
confidence: 99%
“…When demands for postural loads have been alleviated, the stroke-impaired system was capable of generating foot forces that are appropriately controlled in magnitude and direction [ 13 ]. However, this appropriate foot-force control capability was disrupted under more challenging conditions, when individuals post-stroke have to simultaneously control for postural loads in addition to the locomotor task [ 22 , 23 ], comparable to overground/treadmill walking conditions. This inability to modulate braking impulse with reduction in speed can pose safety threats for individuals with chronic post-stroke hemiparesis.…”
Section: Discussionmentioning
confidence: 99%
“…Medium latency responses via the brainstem are likely responsible for these functional postural responses, in combination with the cerebellum, which adapts postural responses for optimality based on preceding experience (Jacobs and Horak, 2007). Although the impaired adaptation of the Ia afferent pathway via the spinal cord has been reported in tasks involving postural control and locomotion in people chronically post-stroke (Liang and Brown, 2015;Liang et al, 2019), they are likely not the main contributor to this observed improvement, as short-latency reflex pathway via the spinal cord is too weak to be functional for postural control.…”
Section: Discussionmentioning
confidence: 99%
“…It would be important to explore the time course of adaptations. Additionally, future studies should address multi-level adaptations by examining the contribution of the altered neural circuitry post-stroke [8,9].…”
Section: Discussionmentioning
confidence: 99%